A Descriptive Study of the Progression of the Metabolic Syndrome in Middle-Aged Chinese Population. (January 2015) - Strand, Mark A.; Will, Theresa; Gu, Xiaoxue; Perry, Judith
This longitudinal study investigated the prevalence of the Metabolic Syndrome (MetS) in middle-aged (44–56 years) men and women in China. The presence of the components of the MetS was determined in a cohort of 643 persons born in 1956, 1960–1961, and 1964 in Shanxi Province China in 2008 and 2012. The rate of MetS in 2008 was 51.63% (95% CI [44.73, 58.48]) and 37.15% (95% CI [32.56, 41.92]) and in 2012 was 50.23% (95% CI [43.35, 57.10]) and 46.26% (95% CI [41.46, 51.11]) for men and women, respectively. Increased blood glucose and triglycerides and decreased high-density lipoprotein for women, and blood glucose and triglycerides for men were the components responsible for the development of MetS from 2008 to 2012. MetS develops differently between men and women. From age 44 to 56, the rate is unchanged among men and increasing among women.